2019
DOI: 10.31026/j.eng.2019.04.07
|View full text |Cite
|
Sign up to set email alerts
|

Application of Waste Lead Acid Battery Plastic to Produce Lightweight Masonry Units

Abstract: The concrete industry consumes millions of tons of aggregate comprising of natural sands and gravels, each year. In recent years there has been an increasing trend towards using recycled aggregate to save natural resources and to produce lightweight concrete. This study investigates the possibility of using waste plastic as one of the components of lead-acid batteries to replace the fine aggregate by 50 and 70% by volume of concrete masonry units. Compared to the reference concrete mix, results demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…It was found that the density decreases by (32.5 and 39.5) % for replacement percentages of (50 and 70) %, respectively, at 28 days. Compressive strength decreased by (28.1and 37.4) % for (50 and 70) % plastic waste, respectively, compared to the reference mixture at 28 days (Aljubori, et al,2019).…”
Section: Literature Reviewmentioning
confidence: 92%
See 2 more Smart Citations
“…It was found that the density decreases by (32.5 and 39.5) % for replacement percentages of (50 and 70) %, respectively, at 28 days. Compressive strength decreased by (28.1and 37.4) % for (50 and 70) % plastic waste, respectively, compared to the reference mixture at 28 days (Aljubori, et al,2019).…”
Section: Literature Reviewmentioning
confidence: 92%
“…Finally, the use of 10 % plastic waste from the volume of coarse aggregate and 5% of nano silica sand powder from the weight of cement in (B-285) led to an increase the absorption up to (10.80) % compared to the reference mix (B-300) which results (4.21) % much less than the requirement of masonry units in IQS 1077/ 1987. The increase in absorption when using plastic aggregate as partial replacement may be attributed to plastic's shape, which leads to an increase in voids that may increase absorption (Aljubori, et al,2019). Figure 6.…”
Section: Absorption Of Concrete Masonry Units (Blocks)mentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing recycled waste would be vital from an environmental and economic aspect. [9], [10]. Natural aggregate resources are becoming increasingly limited due to fast urban expansion, and many old buildings are being destroyed, leading to a considerable decrease in natural resources and a significant rise in construction waste.…”
Section: Introductionmentioning
confidence: 99%
“…(Nandhakumar et al, 2020). This study investigates the possibility of using waste plastic as one of the components of lead-acid batteries to replace the fine aggregate by 50 and 70% by volume of concrete masonry units (Aljubori et al, 2019). This study focused on creating load-bearing concrete masonry units (blocks) that were environmentally friendly, and five concrete mixtures were crushed at the blocks-producing machine (Qasim et al, 2022).…”
Section: Introductionmentioning
confidence: 99%